Delmar's advanced nursing skills DVD-ROM [ - Altman, Gaylene Bouska; Altman, Gaylene Bouska; Morrison, Agnes M. (Thomson/Delmar Learning, 2004)
Containing approximately 150 minutes of step-by-step video ... focusing on venipuncture and starting IV therapy, maintaining IV therapy, blood transfusions, and oxygenation --Container